Comparison of efficacy and safety of ripertamab (SCT400) versus rituximab (Mabthera®) in combination with CHOP in patients with previously untreated CD20‐positive diffuse large B‐cell lymphoma: A randomized, single‐blind, phase III clinical trial. Issue 5 (12th August 2022) - Shi, Yuankai; Zhang, Qingyuan; Hong, Xiaonan; Wang, Zhen; Gao, Yuhuan; Zou, Liqun; Cen, Hong; Gui, Lin; Li, Yufu; Feng, Jifeng; Wang, Zhao; Zhang, Mingzhi; et al.
Abstract: This study compared the efficacy, safety and immunogenicity of ripertamab (SCT400) and rituximab (Mabthera ® ) combined with CHOP as the first‐line treatment for Chinese patients with CD20‐positive diffuse large B cell lymphoma (DLBCL). This is a randomized, patient‐blind, multicenter, active‐control, non‐inferiority study with parallel design. Patients were randomly (2:1) to receive ripertamab combined with CHOP (S‐CHOP) or rituximab (Mabthera ® ) combined with CHOP (R‐CHOP) for up to 6 cycles. The primary endpoint was the Independent Review Committee (IRC) assessed objective response rate (ORR) in full analysis set (FAS) and the per protocol set (PPS). A total of 364 patients (243 in the S‐CHOP and 121 in the R‐CHOP groups) were enrolled in this study. In FAS, IRC‐assessed ORRs were 93.8% (95% confidence interval (CI) 90.0%, 96.5%) and 94.2% (95% CI: 88.4%, 97.6%) in the S‐CHOP and R‐CHOP groups ( p = 0.9633), respectively. The ORR difference between the two groups −0.4% (95% CI: −5.5%, 4.8%) met the pre‐specified non‐inferiority margin of −12%. There were no significant differences between the S‐CHOP and R‐CHOP groups in 1‐year progression‐free survival rates (81.1% vs. 83.2%, p = 0.8283), 1 year event‐free survival rates (56.2% vs. 58.1%, p = 0.8005), and 3‐year overall survival rates (81.0% vs. 82.8%, p = 0.7183). The results in PPS were consistent with those in FAS. The rates of treatment‐emergent adverse events (TEAEs) and ≥ grade 3 TEAEs were 97.9% and 99.2%, 85.2% and 86.0% in the S‐CHOP and R‐CHOP groups, respectively in safety set. The percentage of anti‐drug antibodies positive patients in the S‐CHOP group was numerically lower than the R‐CHOP group (10.9% vs. 16.0%). This study demonstrated that S‐CHOP was not inferior to R‐CHOP in the first‐line treatment of Chinese patients with CD20‐positive DLBCL in efficacy, safety and immunogenecity. S‐CHOP could be an alternative first‐line standard treatment regimen for this patient population.